2001
DOI: 10.1007/s001980170111
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Measurements at the Proximal Phalanges in Male Patients with Psoriatic Arthritis

Abstract: Bone ultrasound parameters at the proximal phalanges of the hands were measured in 55 male patients with psoriatic arthritis (PA) (39 with peripheral radiologic involvement and 16 with axial involvement), comparing the findings with those in 16 rheumatoid arthritis (RA) patients, 20 ankylosing spondylitis (AS) patients and 55 age- and sex-matched normal controls. Mean values of amplitude-dependent speed of sound (Ad-SoS) and ultrasound bone profile score (UBPS) were significantly lower in RA (p < 0.001 and p <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…showed that values were unrelated to disease duration or to ESR and C-reactive protein [55]. Also, in the sample of patients with PsA from India, no correlation was found between BMD and the duration of the disease [56].…”
Section: Discussionmentioning
confidence: 89%
“…showed that values were unrelated to disease duration or to ESR and C-reactive protein [55]. Also, in the sample of patients with PsA from India, no correlation was found between BMD and the duration of the disease [56].…”
Section: Discussionmentioning
confidence: 89%
“…Some investigators concentrated their efforts on an anatomical area 7,8,9,10 . Of note, Falsetti, et al studied the lateral deltoid origin and proposed that sonographic signs of enthesitis at this site may have a high diagnostic specificity 7 .…”
Section: Sonography In the Evaluation Of Enthesitis In Psoriasis And Psamentioning
confidence: 99%
“…Changes in the acoustic properties of the bones of upper extremities have been recently studied [9][10][11][12] with regard to different diseases. Nevertheless, there is little knowledge within the framework of the composite (holistic) model regarding the mechanisms of bone regeneration and the role of bone in the result and complications at replantation of upper extremities.…”
Section: Introductionmentioning
confidence: 99%